ON DIFFERENT TREATMENTS FOR DIFFERENT TYPES OF SYSTEM COMPLEXITY - Tarasenko, F.P. (IJRDO -Journal of Computer Science Engineering, 2017)
A systems view of the world is currently the dominant paradigm inmodern human practice. And in all practical cases the main concern is toovercome difficulties that stem from complexity of a system under consideration.But the “complexities” have various origins of a different nature and thus requiredifferent approaches to tackling each of them. The paper discusses thesedifferences.